Salamanca as Simbolyc Reference: the 21st Century City in Tierra Violenta de Luciano Egido (Castilla. Estudios de Literatura, 2016)
The purpose of this article is to examine the symbolic material and social links between collective memory, identity and the space of Salamanca, in the 21st century through the novel,  Tierra Violenta, by Luciano G. Egido. From this perspective, I propose a reading of this text that helps us to understand how the political and economic circumstances determine the structure of the city; which changes, in turn, the life of their inhabitants. It is a city that, apparently, lives in the past but that isn't immune to the mechanisms rule the 21st century. In this approach, the literary text is a source of different analytical lines for understanding the urban temporalities and the dialectics of both the public project and the urban heritage.